Food territories and reinvention of traditions on Serra Catarinense (SC) colonial kitchen: the experience of the Associação de Agroturismo Acolhida na Colônia - Junqueira, Antonio Hélio (Geografares, 2018)
The study investigates the dynamics and strategies articulated by the rural tourism structuring project in the region of the Serra Catarinense (SC), by the Associação de Agroturismo Acolhida na Colônia, in the search to reintroduce regional food prepartion practices and knowledge. The text is based on qualitative research focused on the collection and discursive analysis of reports produced by different media, selected and disseminated by the investigated association and results in the validation of the pertinence of the adoption of both the concept of invention of the traditions and the practices of agency of memory popular for the imaginary reconstruction of the food territory under study.Keywords: Regional food. Food territories. Traditions.